GERAKAN DAKWAH HIZBUT TAHRIR INDONESIA - Muhammadin Muhammadin (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Hizb ut-Tahrir try to enforce Islamic Shariah throughda‟wastrategy by multiple stages namely; Tatsqif Phase (coaching the cadre), Tafa'ul (interaction) and Istilamul Hukmi (takeover of power). First Phase: Forming a political party that will conduct training the cadre (Marhalah at-Tatsqif). Political party formed will prepare cadres who are acquainted with Islam and want to fight for Islam, these cadres are formed by routine education weekly and monthly, which will convey the ideas and methods of da‟wa of the Hizb in order to establish the framework of the party. The second stage is interaction with the people and encouraged the people to carry the Islamic da'wah. It forms awareness and public opinion on the basis of the ideas and Islamic laws that has been selected and set the Hizb, to serve as thinking people who will encourage him to realize the life reality. The third stage: Stages of Acquisition of Power (Marhalah Istilam Al-Hukm), which is implemented to develop the message of Islam to the world.